Immune modulation of CD4+CD25+ regulatory T cells by zoledronic acid. (December 2016) - Liu, Hsien; Wang, Shih-Han; Chen, Shin-Cheh; Chen, Ching-Ying; Lo, Jo-Lin; Lin, Tsun-Mei
Abstract Background CD4+ CD25+ regulatory T (Treg) cells suppress tumor immunity by inhibiting immune cells. Manipulation of Treg cells represents a new strategy for cancer treatment. Zoledronic acid (ZA), a nitrogen-containing bisphosphonate, inhibits the expression of receptor activator of nuclear factor kappa-B ligand (RANKL) on osteoblasts to inhibit osteoclastogenesis. In a mouse model of bisphosphonate-related osteonecrosis of the jaw, administration of ZA suppressed Treg-cell activity and activated inflammatory Th17 cells. However, the interaction between ZA and Treg cells remained unclear. This study investigated the immune modulation of Treg cells by ZA. Methods Flow cytometry was used to analyze the phenotypic and immunosuppressive characteristics of Treg cells treated with ZA. Chemotactic migration was evaluated using transwell assays. Quantitative real-time PCR (qRT-PCR) was used to investigate the effect of ZA on the expression of suppressive molecules by Treg cells. Results Proliferation of isolated Treg cells in culture was inhibited by ZA, although ZA did not induce apoptosis. qRT-PCR and flow cytometry showed that ZA significantly downregulated the expression of CCR4, CTLA4, PD-1 and RANKL on Treg cells. Chemotactic migration and immunosuppressive functions were also significantly attenuated in Treg cells pretreated with ZA, and these effects were dose-dependent. Co-culture with Treg cells significantly increased the migration rate of breast cancer cells, while pretreatment of Treg cells with ZA attenuated this effect. Conclusions Our findings demonstrated that ZA acted as an immune modulator by significantly inhibiting the expansion, migration, immunosuppressive function and pro-metastatic ability of Treg cells. Immunomodulation of Treg cells by ZA represents a new strategy for cancer therapy.